How to Promote Skin Repair? In-Depth Look at Pharmaceutical and Cosmetic Strategies - Ana Torres; Liliana Rego; Márcia S. Martins; Marta S. Ferreira; Maria T. Cruz; Emília Sousa; Isabel F. Almeida (MDPI AG, 2023)
Skin repair encompasses epidermal barrier repair and wound healing which involves multiple cellular and molecular stages. Therefore, many skin repair strategies have been proposed. In order to characterize the usage frequency of skin repair ingredients in cosmetics, medicines, and medical devices, commercialized in Portuguese pharmacies and parapharmacies, a comprehensive analysis of the products' composition was performed. A total of 120 cosmetic products, collected from national pharmacies online platforms, 21 topical medicines, and 46 medical devices, collected from INFARMED database, were included in the study, revealing the top 10 most used skin repair ingredients in these categories. A critical review regarding the effectiveness of the top ingredients was performed and an in-depth analysis focused on the top three skin repair ingredients pursued. Results demonstrated that top three most used cosmetic ingredients were metal salts and oxides (78.3%), vitamin E and its derivatives (54.2%), and Centella asiatica (L.) Urb. extract and actives (35.8%). Regarding medicines, metal salts and oxides were also the most used (47.4%) followed by vitamin B5 and derivatives (23.8%), and vitamin A and derivatives (26.3%). Silicones and derivatives were the most common skin repair ingredients in medical devices (33%), followed by petrolatum and derivatives (22%) and alginate (15%). This work provides an overview of the most used skin repair ingredients, highlighting their different mechanisms of action, aiming to provide an up-to-date tool to support health professionals' decisions.